Use of a LC-DAD-QTOF system for the characterization of the phenolic profile of the argentinean plant Zuccagnia punctata and of the related propolis: New biomarkers. (June 2017) - Solorzano, Eliana Rita; Bortolini, Claudio; Bogialli, Sara; Di Gangi, Iole Maria; Favaro, Gabriella; Maldonado, Luis; Pastore, Paolo
Highlights: Characterization of the phenolic profile of Zuccagnia punctata by LC-DAD-QTOF. The identification of eleven new compounds in Z. punctata was proposed . Two dihydrochalcones was described for the first time as biomarkers of Z. punctata. The botanical origin of some Z. punctata -related propolis has been revealed. Abstract: Argentinean northwestern propolis were included into the national Food Code, some of that were sometimes associated with Zuccagnia punctata, an endemic plant with interesting biological properties. An analytical protocol for characterizing the phenolic profile of Z. punctata by LC coupled to DAD-QTOF detection systems was proposed. Mass spectrometric and chromatographic selectivity allowed to recognize various compounds including isomers. Eleven compounds never mentioned before for this shrub were highlighted. Among them, two uncommon dihydrochalcones, i.e. 4′-hydroxy-2′-methoxydihydrochalcone and 2′, 4′-dihydroxydihydrochalcone, were described for the first time as major constituents of Z. punctata, suggesting a peculiar biosynthetic pathway. Only the two propolis collected in the "Del Monte" phytogeographical region showed large amounts of molecules present in Z. punctata, which were proposed as markers of propolis type Z. punctata. Since Z. punctata exhibits a very interesting bioactivity, propolis derived from this plant can be used as nutraceutical food.